Evaluation of Psychometric Properties of Hindi Versions of Geriatric Depression Scale and Patient Health Questionnaire in Older Adults. Issue 4 (July 2021) - Mehra, Aseem; Agarwal, Arun; Bashar, Mohammad; Grover, Sandeep
Background: A limited number of studies have evaluated the psychometric properties of rating scales used to assess depression in the older adults. The present study aimed to assess the validity of the Hindi Geriatric Depression Scale (GDS, 30, 15, 10, 5, 4, and 1 item version) and Hindi Patient Health Questionnaire (nine and two items version) in a group of older adults residing in a rural community. Methods: The psychometric properties of these scales were assessed against the diagnosis of depression a qualified psychiatrist made by using a semistructured interview. Results: Total 125 older adults were recruited from a rural community, with a mean age of 65.5 (SD: 6.4) years. The prevalence of depression was 36.8% as per the evaluation by the psychiatrist. When the agreement of different scales with the clinicians' diagnosis was evaluated, it was seen that sensitivity, specificity, and Cohen Kappa value of GDS-30 and 15 were better than the other scales used to assess depression. When the sensitivity and specificity were evaluated using newer cutoffs, the specificity and sensitivity of GDS-30 were more than that of other scales. Conclusion: Hindi version of GDS-30 with a cutoff of 13 has excellent psychometric properties.